Marketing de influencers: percepción de empresarios y consumidores frente a una propuesta publicitaria (2018)
Influencer marketing has been established in recent years as one of the most effective advertising strategies in generating engagement with the customer through social networks and seeks to connect the consumer with the brand through trust, under the principle of the message "word of mouth"; in such a way that users no longer see a figure advertising a product but a friend recommending it. This work analyzes the influencers' marketing from its three agents; the entrepreneur, the influencer and the consumer, in order to identify those aspects that make this strategy effective in the young users of Cali city. . An exploratory-type qualitative research was carried out by means of which relevant information was gathered about how this strategy operates from the entrepreneur's point of view, what aspects a content needs to impact the consumers according to the influencers, as well as the likes, attributes and experiences sought by consumers by the two agents mentioned above